ANALISIS SEMIOTIKA ROLAND BARTHES PADA COVER MAJALAH TEMPO EDISI 12 DESEMBER 2020 "POLISI VERSUS FPI" - Irsan Adrianda; Akhyarsyah Agya (Communicative : Jurnal Dakwah dan Komunikasi, 2023)
Presentation and delivery of information through the mass media has now undergone many developments from time to time. With online-based information technology, mass media is present in delivering messages in the form of online. Print media is also making developments that are now available online and can be accessed by anyone, anywhere, without having to buy in printed form. Tempo, with its magazine that provides news, is well known for its criticism of several parties. Tempo magazine cover or cover that displays a fairly unique illustration image and contains a lot of meaning in conveying information. This study aims to determine the meaning of the messages contained in the cover of the 12 December 2020 edition of Tempo magazine. The method used in this study is a textual research method with a semiotic analysis approach using the Roland Barthes' model, denotation meaning, connotation meaning, and myth meaning. The results of this study refer to the meaning of the message from the cover of the 12 December 2020 edition of Tempo magazine using the semiotic analysis approach of Roland Barthes' model. In this case, Tempo as a media dared to criticize and insinuate related parties in the magazine cover. And the public or the audience who receive the message can interpret the message itself, but this situation divides the public's attention and creates a space for wrong interpretation.